Does IFRS convergence improve earnings informativeness? An analysis from the book-tax tradeoff perspective - Chan, K. Hung; Lin, Kenny Z.; Mo, Phyllis L. L.; Wong, Pauline W. (Accounting and business research, 2023)
Exploiting the convergence of tax-based accounting standards to the judgement-based International Financial Reporting Standards (IFRS) as an information shock, this study examines whether the decrease in book-tax conformity improves earnings informativeness in China from the book-tax tradeoff perspective. Using A-share firms which experience this drastic regulatory change as the treatment firms and B-share firms which are not subject to such change as the benchmark firms, we find a significant decrease in the earnings informativeness for A-share firms but not B-share firms, and that the decrease is most pronounced for firms with strong financial reporting incentives. Additional analyses reveal that the decreases in earnings informativeness are due to financial reporting changes rather than changes in economic conditions. Our results shed light on the importance of considering underlying institutional factors in assessing the impact of changes in financial reporting on earnings quality.